Case Report: When all claims that it is necrotizing fasciitis but Point of care ultrasound (POCUS) proves the opposite! - Hadiel Kaiyasah; Maryam Al Ali (POCUS Journal, 2018)
Soft tissue ultrasound (ST-USS) has been shown to be of utmost importance in assessing patients with soft tissue infections in the emergency department or critical care unit. It aids in guiding the management of soft tissue infection based on the sonographic findings.